God according to God : a physicist proves we've been wrong about God all along - Schroeder, Gerald L. (New York, NY : HarperOne, 2009)
A renowned scientist and author combines decades of scientific research and biblical study to present a groundbreaking new paradigm of how to understand God.
A few words about what God is not -- The origins of life : one reason I know there is a God -- The unlikely planet Earth : finding a friendly home in a challenging universe -- Nature rebels : God grants nature a mind of its own -- A repentant God? How to understand a God that has regrets -- Arguing with God : we are partners with God and partners can disagree -- In defense of God : understanding God through the book of Job -- Life and death : two perspectives on one reality -- The desert tabernacle : a model for a universe built of love -- Knowing truth in your heart : a tale of love -- Understanding the merciful God of the Bible : golden apples in a silver dish -- Partners with God : working with a God that will be.
Includes bibliographical references (p. [231]-236) and indexes.
Keywords: Religion and science; God -- Attributes; God -- Proof, Teleological